2012
DOI: 10.1186/1471-244x-12-1
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress symptoms and health-related quality of life: a two year follow up study of injury treated at the emergency department

Abstract: BackgroundAmong injury victims relatively high prevalence rates of posttraumatic stress disorder (PTSD) have been found. PTSD is associated with functional impairments and decreased health-related quality of life (HRQoL). Previous studies that addressed the latter were restricted to injuries at the higher end of the severity spectrum. This study examined the association between PTSD symptoms and health-related quality of life (HRQoL) in a comprehensive population of injury patients of all severity levels and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
216
7
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(243 citation statements)
references
References 45 publications
19
216
7
1
Order By: Relevance
“…In our study the EQ-5D summary scores showed that injury patients with had a mean utility loss of 0.23 -0.45 compared to injury patients without PTSD. This corresponds with the utility loss of 0.23-0.33 of patients with PTSD compared to those without found by Haagsma et al in a similar sample of injury patients [12].…”
Section: J Depress Anxietysupporting
confidence: 82%
See 2 more Smart Citations
“…In our study the EQ-5D summary scores showed that injury patients with had a mean utility loss of 0.23 -0.45 compared to injury patients without PTSD. This corresponds with the utility loss of 0.23-0.33 of patients with PTSD compared to those without found by Haagsma et al in a similar sample of injury patients [12].…”
Section: J Depress Anxietysupporting
confidence: 82%
“…The lowresponse rates may have led to selection bias and in its turn to under-or overestimation of the prevalence of PTSD [20]. In the case of our study there was the risk of overestimation, since women were overrepresented while female gender is thought to be a predictor of PTSD [1,12,29,30]. Also patients who demonstrated PTSD symptoms at a previous time point tended to respond to the questionnaire more often, who are likely to still have PTSD at later time points.…”
Section: Strengths and Limitationsmentioning
confidence: 68%
See 1 more Smart Citation
“…Authors were contacted if it was unclear whether samples overlapped. To avoid bias, studies using UHR individuals recruited solely from prisons, or young offender institutions were excluded 22 as substance use in these groups tends to be higher than in the general population 23.…”
Section: Methodsmentioning
confidence: 99%
“…21 During the interviews, at the time of data collection, some individuals reported a delay in the results of the exams of the source patient, with this situation generating an intense feeling of fear and anguish. Some authors have also shown this in their findings, reporting that waiting times for definitive blood test results cause anxiety and increase the duration of some psychiatric consequences following the exposure.…”
mentioning
confidence: 99%